Detection of the Anaerobic Threshold in Endurance Sports: Validation of a New Method Using Correlation Properties of Heart Rate Variability - Rogers B. Bruce; Giles D. A. David; Draper N. Nick; Mourot L. Laurent; Gronwald Th. Thomas (2021, 2021)
Title screen